Deep Batch Active Learning by Diverse, Uncertain Gradient Lower Bounds - Ash, Jordan T.; Zhang, Chicheng; Krishnamurthy, Akshay; Langford, John; Agarwal, Alekh (Eighth International Conference on Learning Representations (ICLR), 2020)
We design a new algorithm for batch active learning with deep neural network models. Our algorithm, Batch Active learning by Diverse Gradient Embeddings (BADGE), samples groups of points that are disparate and high-magnitude when represented in a hallucinated gradient space, a strategy designed to incorporate both predictive uncertainty and sample diversity into every selected batch. Crucially, BADGE trades off between diversity and uncertainty without requiring any hand-tuned hyperparameters. We show that while other approaches sometimes succeed for particular batch sizes or architectures, BADGE consistently performs as well or better, making it a versatile option for practical active learning problems.